High-Density Surface EMG Decomposition: Achievements, Challenges, and Concerns - Maoqi Chen; Ping Zhou (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
High-density surface electromyography (EMG) decomposition provides a valuable non-invasive approach to accessing key motor unit information for a range of applications. This communication summarizes significant advances in high-density surface EMG decomposition, and discusses several considerable challenges and persistent concerns in this field, particularly regarding dynamic and real-time high-density surface EMG decomposition, as well as evaluating the reliability of the decomposed motor units. As varying high-density surface EMG decomposition programs are increasingly developed, we call for open access or sharing of source code and testing data developed by different groups. We believe such efforts can greatly facilitate collaboration, clarify concerns, address challenges, and thus motivate further development and application of high-density surface EMG decomposition.